2024
DOI: 10.3389/fimmu.2024.1341600
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological, immunological, and inflammatory features of long COVID

Karen Bohmwald,
Benjamín Diethelm-Varela,
Linmar Rodríguez-Guilarte
et al.

Abstract: The COVID-19 pandemic continues to cause severe global disruption, resulting in significant excess mortality, overwhelming healthcare systems, and imposing substantial social and economic burdens on nations. While most of the attention and therapeutic efforts have concentrated on the acute phase of the disease, a notable proportion of survivors experience persistent symptoms post-infection clearance. This diverse set of symptoms, loosely categorized as long COVID, presents a potential additional public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 358 publications
(533 reference statements)
0
1
0
Order By: Relevance
“…However, we did not cover various phenomena of canonical inflammation related to LC, which can manifest in different organs and tissues of patients suffering from LC. These issues have been addressed in review articles by other authors, including [ 285 , 319 , 320 , 321 , 322 ]. Another aspect of canonical inflammation in LC, which was not included in the aims and objectives of our study, is considering LC as a risk factor for the onset of various inflammatory diseases or the progression of existing inflammatory diseases [ 323 , 324 , 325 , 326 , 327 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, we did not cover various phenomena of canonical inflammation related to LC, which can manifest in different organs and tissues of patients suffering from LC. These issues have been addressed in review articles by other authors, including [ 285 , 319 , 320 , 321 , 322 ]. Another aspect of canonical inflammation in LC, which was not included in the aims and objectives of our study, is considering LC as a risk factor for the onset of various inflammatory diseases or the progression of existing inflammatory diseases [ 323 , 324 , 325 , 326 , 327 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, it is involved in innate immunity [419], especially in mucosa [420], and bears similarities to lipopolysaccharide-binding protein (LPS being a molecule that can trigger fibrinaloid formation [191,192,421]). BPIB1 can also inhibit Epstein-Barr virus proliferation [422][423][424] (something of major potential relevance in Long COVID [425][426][427]). Overall, the fact that it is so concentrated in fibrinaloid microclots in the case of Long COVID is thus very notable.…”
Section: Amyloidogenicity Of Proteins 'Entrapped' In Microclotsmentioning
confidence: 99%
“…Furthermore, the injury inflicted upon endothelial cells by nucleocapsid and envelope proteins triggers cytokine induction and immune activation. Additionally, the prolonged presence of COVID-19 infection and immune dysregulation may lead to the reactivation of other viruses (Epstein-Barr virus, human herpesvirus 6, and cytomegalovirus) and the onset of bacterial diseases (tuberculosis) [ 60 ]. It is also suggested that the autonomic nervous system may be directly damaged by the SARS-CoV-2 virus or by an autoimmune process, leading to dysautonomia [ 58 ].…”
Section: Introductionmentioning
confidence: 99%